Confronting SUSY GUT With Dark Matter, Sparticle Spectroscopy and Muon (g − 2) - Gómez, Mario E.; Lola, Smaragda; Ruiz de Austri, Roberto; Shafi, Qaisar (Frontiers in Physics, 2018)
We explore the implications of LHC and cold dark matter searches for supersymmetric particle mass spectra in two different grand unified models with left-right symmetry, SO(10) and SU(4)_c × SU(2)_L × SU(2)_R (4-2-2). We identify characteristic differences between the two scenarios, which imply distinct correlations between experimental measurements and the particular structure of the GUT group. The gauge structure of 4-2-2 enhances significantly the allowed parameter space as compared to SO(10), giving rise to a variety of coannihilation scenarios compatible with the LHC data, LSP dark matter and the ongoing muon g-2 experiment.